2013
DOI: 10.1007/978-3-642-38267-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Depth Maps with Segment-Based Homogeneous Diffusion

Abstract: Abstract. The efficient compression of depth maps is becoming more and more important. We present a novel codec specifically suited for this task. In the encoding step we segment the image and extract betweenpixel contours. Subsequently we optimise the grey values at carefully selected mask points, including both hexagonal grid locations as well as freely chosen points. We use a chain code to store the contours. For the decoding we apply a segment-based homogeneous diffusion inpainting. The segmentation allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…A similar approach by Mainberger et al [6] for cartoon-like images also selects mask pixels along edges. Hoffmann et al [7] extended this idea by explicitly storing segment boundaries with chain codes and selecting mask pixels on a hexagonal grid.…”
Section: B Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar approach by Mainberger et al [6] for cartoon-like images also selects mask pixels along edges. Hoffmann et al [7] extended this idea by explicitly storing segment boundaries with chain codes and selecting mask pixels on a hexagonal grid.…”
Section: B Related Workmentioning
confidence: 99%
“…The result of this edge-aware homogeneous diffusion inpainting gives us a flow field with discontinuities along edges E and smooth transitions in between. In contrast to the segment-based homogeneous diffusion of Hoffmann et al [7], our method allows arbitrary edge structures and does not require a segmentation with closed contours.…”
Section: Edge-aware Homogeneous Diffusion Inpaintingmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,4,5,6,7]), most of the early works do not consider applications in image compression. Only recently it has been shown that edge-or segment-based homogeneous diffusion approaches can beat JPEG 2000 for cartoon-like im-1 ages [8], as well as for depth maps [9,10,11]. Apart from these linear, featurebased approaches, there are some attempts to use nonlinear PDEs for image compression.…”
Section: Introductionmentioning
confidence: 99%